Brain activation during visual working memory correlates with behavioral mobility performance in older adults - Kawagoe, Toshikazu; Suzuki, Maki; Nishiguchi, Shu; Abe, Nobuhito; Otsuka, Yuki; Nakai, Ryusuke; Yamada, Minoru; Yoshikawa, Sakiko; Sekiyama, Kaoru (Frontiers in Aging Neuroscience, 2015)
Functional mobility and cognitive function often decline with age. We previously found that functional mobility as measured by the Timed Up and Go Test (TUG) was associated with cognitive performance for visually-encoded (i.e. for location and face) working memory (WM) in older adults. This suggests a common neural basis between TUG and visual WM. To elucidate this relationship further, the present study aimed to examine the neural basis for the WM-mobility association. In accordance with the well-known neural compensation model in aging, we hypothesized that “attentional” brain activation for easy WM would increase in participants with lower mobility. The data from 32 healthy older adults were analyzed, including brain activation during easy WM tasks via functional Magnetic Resonance Imaging and mobility performance via both TUG and a simple walking test. WM performance was significantly correlated with TUG but not with simple walking. Some prefrontal brain activations during WM were negatively correlated with TUG performance, while positive correlations were found in subcortical structures including the thalamus, putamen and cerebellum. Moreover, activation of the subcortical regions was significantly correlated with WM performance, with less activation for lower WM performers. These results indicate that older adults with lower mobility used more cortical (frontal) and fewer subcortical resources for easy WM tasks. To date, the frontal compensation has been proposed separately in the motor and cognitive domains, which have been assumed to compensate for dysfunction of the other brain areas; however, such dysfunction was less clear in previous studies.The present study observed such dysfunction as degraded activation associated with lower performance, which was found in the subcortical regions. We conclude that a common dysfunction -compensation activation pattern is likely the neural basis for the association between visual WM and functional mobility.